Advantages and Weaknesses of Online Lecturing During Covid 19 Outbreak in Indonesia: Students’ Perception - Cahyadi, Ani (Southeast Asian Journal of Islamic Education, 2021)
This study researches the advantages and weaknesses of applying online lecturing during the pandemic period. The purposes of this research are to describe the platforms and learning applications used by lecturer-students and the advantages and weaknesses in having online lecturing. This study used descriptive case study design with 117 participants. The samples were the Islamic University of Antasari Banjarmasin, the Islamic University of Walisongo Semarang, and the University of PGRI Semarang. The writer used data reduction, data display, and data conclusion. The writer analyzed the data used a tool of qualitative data namely ATLAS.TI8. The results of this research show that the applications in conducting the online lecture are; google classroom, zoom, google meet, LMS Post Graduate, Youtube, WAG, and telegram. The advantages are that online lecturing is easy to do anywhere and more flexible, it saves pocket money, energy, time and place, materials could be repeated and saved, it only takes short time and is also fun, paperless and timeless, no need to stay at the campus, and it saves the transportation fee. The weaknesses are the time is sometimes very limited and students’ quota is sometimes insufficient, the voice is unclear, the network is easy to trouble, there is no direct feedback and evaluation, it needs adequate smartphone and quota, it has more assignments and less discussion, and the materials are difficult to understand and too short explanation.